1869 N.M. Laws 72 - (:unkn) unknown (My University, 1869)
Ch. 32, §§ 1-2: Prohibited the carry of deadly weapons. Deadly weapons shall be defined as all classes of pistols, revolver, repeater, derringer, or any other kind of pistol, Bowie-knives, daggers, poniards, butcher knives, dirks, "all weapons in which cuts can be give or by which wounds can be inflicted by thrusting," sword-canes, slung-shots, and any other kinds of deadly weapons.
Keywords: CARRY; DEFINITIONS